Η μητρόπολη Καστοριάς τον 16ο και 17ο αιώνα. Προσθήκες και διορθώσεις στον επισκοπικό της κατάλογο [SPYROS CHR. KARYDIS, The Metropolis of Kastoria at 16th and 17th centuries. Additions and corrections to its episcopal catalogue] - Καρύδης Σπύρος Χρ. (Μακεδονικά, 2011)
This study constitutes a small contribution to the ecclesiastical history ofKastoria at the 16th and 17th centuries and it aims in the completion andcorrection of its episcopal catalogue in a period for which in the existing bibliography the information is very little and sometimes contradictory.The study is supported in new, unknown until now, and unexploited archival material, emanating from the Historical Archive of Corfu and the Archiveof Gennadeios’ Library, as well as in the review of known sources and mainlythe codex of the Metropolis of Kastoria, that covers the period 1563-1665(EBE 2752), which contains fragments of acts and decisions of metropolitancourt with the signature of each metropolite.